The markets for non-timber forest products in the humid forest zone of Cameroon - Ndoye, O.; Ruíz Pérez, M.; Eyebe, A. (1998)
Many rural dwellers in tropical regions depend on non-timber forest products (NTFPs) for their livelihood and their income needs. Local markets play an important role in enabling forest-dependent households to realize a significant part of their cash income through sale of NTFP's. Increase urbanization (as a result of rural to urban migration) is a significant factor that expands the size of local NTFP markets. This paper focuses on local markets and on market intermediaries who facilitate the coordination (or the matching) of supply and demand of NTFPs by providing market outlets to farmers and guaranteeing a source of domestic supply of NTFPs for consumers. It presents the results of a study which analysed the four main NTFPs sold in the humid forst zone of Cameroon.(Dacryodes edulis, Irvingia spp., Cola acuminata and Ricinodendra heudelotii). The study found that the quantity of NTFPs marketed is significant, amounting to at least US$1.75 million in the first half of 1995. More than 1,100 traders, mainly women, are engaged in the distribution of NTFPs. Furthermore, the marketing margins obtained by traders vary between 16% (for Dacryodes edulis) and 30% (for Irvingia spp.). of the value of slaes. Thus the study confirms the role of NTFPs as a source of employment and income not only for gatherers but also for traders, and suggests the need and potential for developing these markets.